From project portfolios to institutional strategy: mainstreaming climate resilience in agricultural research at CGIAR - Choptiany, J.; Tremper, O.; Jafflin, Z.; Myers, S.; Hernandez, R.; Ledermann, S. (2025)
Agricultural research institutions face mounting pressure to demonstrate climate impact, yet lack systematic approaches to assess and strategically reorient their portfolios. This perspective presents a four-method portfolio analysis framework—combining discourse analysis, publication review, key informant interviews, and stakeholder mapping. The framework was used to assess the International Institute of Tropical Agriculture’s (IITA) 2013–2025 climate portfolio considering new strategic planning. The results of the review revealed five transferable lessons for research organizations: first, reduce the focus on adaptation alone to also include mitigation; second, close gaps between what is documented versus what is undertaken in practice to strengthen policy relevance; third, address the lack of deeper integration of gender and youth; fourth, strengthen institutional capacities to affect policy change; and fifth, advance collaborations across institutes to better address the multidimensionality of climate change impacts and opportunities. Beyond IITA, applying such a portfolio analysis framework is expected to significantly strengthen the ability of institutions to navigate the evolving climate finance landscape and support strategic reorientations in a coherent and impactful way. The approach offers other research institutions a replicable method to move from climate-relevant projects toward comprehensive institutional climate strategies.